BRIDGING THE LACUNA: ADDRESSING LINGUISTIC GAPS AND EXPLORING SOLUTIONS - Abdullayeva , Nozima Komiljon qizi; Ahunjanova, Mohinur Sohibjon qizi; Botirova, Zebo (Educational Research in Universal Sciences, 2023)
Language, as a complex and dynamic system, serves as a cornerstone of human communication. However, within the intricate tapestry of linguistic diversity, there exist gaps and lacunae that pose challenges to effective communication and understanding. This article explores the lacuna problems in linguistics, delves into their causes, and proposes potential solutions to bridge these gaps.